Pengaruh Literasi Keuangan, Transparansi Pengelolaan Usaha dan Pengendalian Internal terhadap Kinerja Keuangan UMKM - Fitri Nadia Salsabila; Sri Trisnaningsih (ARBITRASE: Journal of Economics and Accounting, 2026)
This study aims to analyze the influence of financial literacy, business management transparency, and internal control on the financial performance of culinary Micro, Small and Medium Enterprises (MSMEs) in Menganti Sub-district, Gresik Regency. The study adopted a quantitative approach with primary data collected through questionnaires. The population comprised 398 registered culinary MSMEs, with a sample of 80 respondents selected using simple random sampling based on the Slovin formula. Data analysis was performed using multiple linear regression with SPSS. The results indicate that: (1) financial literacy has a positive and significant effect on MSME financial performance (t=8.842; sig.=0.000); (2) business management transparency has a positive and significant effect on MSME financial performance (t=2.503; sig.=0.014); (3) internal control has a positive and significant effect on MSME financial performance (t=2.477; sig.=0.015); and (4) all three variables simultaneously have a significant effect on MSME financial performance (F=167.947; sig.=0.000). The Adjusted R Square of 0.864 indicates that 86.4% of the variation in MSME financial performance is explained by the three independent variables. These findings affirm that strengthening financial literacy, implementing business management transparency, and applying internal control collectively contribute significantly to improving the financial performance of culinary MSMEs.